Impact of Essential Cinnamon Oils on the Qualitative Attributes of Chicken Eggs at Different Storage Temperatures - Vidyarthi, A. K.; Mendiratta, S. K.; Biswas, A. K.; Talukdar, S.; Agrawal, R. K.; Chand, S. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during during November, 2021 to January, 2023 at the Division of Livestock Products Technology, ICAR-Indian Veterinary Research Institute, Izatnagar, Bareilly, Uttar Pradesh, India to investigate the suitability of cinnamon essential oils sprays for maintaining the quality of eggs during diffrent storage conditons (27±5°C and 4±1°C). The freshly laid, unwashed, chicken shell eggs were procured from local poultry farms in Bareilly and used for the experiments. The eggs immediately after collection were labeled and weighed. Fresh eggs were analyzed within 2–3 hours of laying. The Control sample eggs and Cinnamon essential oils sprays treated eggs were evaluated on day 0, 10, 20, 30, 40, 50, and 55 at refrigeration (4±1°C) and room temperature (27±5°C). The Cinnamon treated eggs samples had significantly lowered (p<0.05) egg weight loss, air cell depth, egg yolk weight, yolk index, haugh unit, lipid peroxidation value, yoik pH, albumen pH and egg surface, albumen, yolk APC value as camapre to control egg sample. The overall sensory parameters were significanty more acceptable in treaed eggs as campare to control sample. The Cinnamon essential oils played a significant role in the maintenance of the quality parameters of eggs, treated eggs should be kept at 4±1°C for up to 40 days and at 27±5°C for up to 20 days.